Immunogenicity of Immunotoxins Containing Pseudomonas Exotoxin A: Causes, Consequences, and Mitigation - Mazor, Ronit; Pastan, Ira (Frontiers in Immunology, 2020)
Immunotoxins are cytolytic fusion proteins developed for cancer therapy, composed of an Fv or Fab that binds to a cancer cell and a protein toxin fragment that kills the cell. Pseudomonas exotoxin A (PE) is a potent toxin that is used for the killing moiety in many immunotoxins.Moxetumomab Pasudotox (Lumoxiti) contains an anti-CD22 Fv and a 38 kDa portion of PE. Lumoxiti was discovered in the Laboratory of Molecular Biology at the U.S. National Cancer Institute and co-developed with Medimmune/AZ to treat hairy cell leukemia. In 2018 Lumoxiti was approved by the FDA for the treatment of drug-resistant Hairy Cell Leukemia. The Laboratory of Molecular Biology also developed immunotoxins targeting mesothelin (SS1P and LMB-100) and CD25 (LMB-2). These immunotoxins have structures similar to Lumoxiti. LMB-100 is a de-immunized variant of the toxin with an antibody that targets mesothelin and is now being evaluated in clinical trials for the treatment of mesothelioma and pancreatic cancer. Due to the bacterial origin of the killing moiety, immunotoxins containing PE are highly immunogenic in patients with normal immune systems, but much less immunogenic in patients with hematologic malignancies, whose immune systems are often compromised. Here we review the immunogenicity of PE immunotoxins in mice and patients, the development of anti-drug antibodies (ADAs), their impact on drug availability and their effect on clinical efficacy. Efforts to mitigate the immunogenicity of immunotoxins will be described including rational design to identify, remove or suppress B cell or T cell epitopes and combination of immunotoxins with immune modulating drugs.